Vitamin E Prevents Lipid Raft Modifications Induced by an Anti-cancer Lysophospholipid and Abolishes a Yap1-mediated Stress Response in Yeast - Bitew, Teshager (American Society for Biochemistry and Molecular Biology, 2010)
We have previously established that the anti-cancer lysophospholipid edelfosine (1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine, Et-18-OCH(3)) induces cell death in yeast by selective modification of lipid raft composition at the plasma membrane. In this study we determined that α-tocopherol protects cells from the edelfosine cytotoxic effect, preventing the internalization of sterols and the plasma membrane proton pump ATPase, Pma1p. Two non-mutually exclusive hypotheses were considered to explain the protective effect of α-tocopherol: (i) its classical antioxidant activity is necessary to break progression of lipid peroxidation, despite the fact Saccharomyces cerevisiae does not possess polyunsaturated fatty acids and (ii) due to its complementary cone shape, insertion of α-tocopherol could correct membrane curvature stress imposed by edelfosine (inverted cone shape). We then developed tools to distinguish between these two hypotheses and dissect the structural requirements that confer α-tocopherol its protective effect. Our results indicated its lipophilic nature and the H donating hydroxyl group from the chromanol ring are both required to counteract the cytotoxic effect of edelfosine, suggesting edelfosine induces oxidation of membrane components. To further support this finding and learn more about the early cellular response to edelfosine we investigated the role that known oxidative stress signaling pathways play in modulating sensitivity to the lipid drug. Our results indicate the transcription factors Yap1 and Skn7 as well as the major peroxiredoxin, Tsa1, mediate a response to edelfosine. Interestingly, the pathway differed from the one triggered by hydrogen peroxide and its activation (measured as Yap1 translocation to the nucleus) was abolished by co-treatment of the cells with α-tocopherol.